Development Interactive Teaching Materials with Google Sites Website-Based Media in Islamic Cultural History Subjects at Madrasah Aliyah - Agustin, Siti Maulidiya; Murhayati, Sri; Alwizar, Alwizar (Journal of English Language and Education, 2025)
This study aims to explore the development of interactive teaching materials using website-based media (Google sites) for Islamic Cultural History subjects at Islamic Senior High School. This research employs the Research and Development (RD) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques include observation, interviews, questionnaires, tests, and documentation. The collected data were analyzed using descriptive analysis techniques, including expert validation questionnaire analysis, user validation, and student responses, all processed in accordance with research and development procedures. Based on the research findings, this development was carried out in five stages: analysis, design, development, implementation, and evaluation. The analysis stage involved curriculum analysis, student analysis, and needs assessment. The design stage included the preparation of learning materials, selection of media, choice of format, and initial design. The development stage involved validation by experts, including media experts, subject matter experts, and Islamic Cultural History teachers. The validation results were as follows: media experts (88.3%, categorized as highly valid), subject matter experts (92.8%, highly valid), and Islamic Cultural History teachers (95.6%, highly valid). During the implementation stage, activities such as pretests, trial implementations, explanations, in-depth material discussions, and posttests were conducted. The overall pretest and posttest results showed a significant improvement, with an average pretest score of 54.09 and a posttest score of 93.71. The student trial results indicated the following ratings: material aspect (83.29%, highly practical), language aspect (83.14%, highly practical), presentation aspect (81.57%, highly practical), and usefulness aspect (85.10%, highly practical). Thus, it can be concluded that the interactive teaching materials using website-based media (Google sites) for the Islamic Cultural History subject, specifically on the topic of the Khulafaur Rashidin, achieved an overall validity percentage of 83.27%, indicating high practicality. The evaluation stage, based on pretest and posttest results, demonstrated a significant improvement in students' learning outcomes in Islamic Cultural History when using the interactive teaching materials Website-based using Google sites.